Analysis of Inpatient Care Service Quality in Hospitals Based on National Standards: A Literature Review - Huwae, Militya; Raden, Jaka Sarwadhamana; Pramesti, Listia Anggi; Julita, Fanesya Rahma; Alkhansa, Salamah Noor; Anwar, Aulia Vidya Nuril; Korina, Evrilia; Pitriani, Dia; Trisardewi, Sartika; Wlakusa, Haula; Kedeikoto, Petrus (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Service quality is the effort to fulfill customer needs and desireswhile ensuring accurate delivery to meet customer expectations. Healthcareprofessionals must consider various factors that influence service quality,particularly in inpatient care settings. Objective: This study aims to assess thequality of inpatient services in hospitals based on national standards outlined inthe Indonesian Ministry of Health Regulation (Kepmenkes) No. 129 of 2008concerning minimum service standards for hospitals. Results: This researchadopts a Literature Review approach using the PICOST method for problemanalysis and article selection. The study follows the PRISMA (Preferred ReportingItems for Systematic Reviews and Meta-Analyses) method, ensuring a systematicreview process. A total of 11,674 journal articles published between 2020 and2023 were retrieved from Google Scholar, PubMed, and ScienceDirect, and fivearticles meeting the inclusion criteria were selected. The analysis highlights keyfactors influencing hospital service quality, including responsiveness, assurance,reliability, empathy, and tangible aspects. Conclusion: The implementation ofminimum service standards and a focus on five dimensions of patient satisfactionresponsiveness, assurance, reliability, empathy, and tangible aspects serve aseffective strategies to enhance patient satisfaction and loyalty in hospital inpatientservices.